2003
DOI: 10.1177/0143034303024002006
|View full text |Cite
|
Sign up to set email alerts
|

Access to Structural Similarity in the Analogical Problem Solving of Children

Abstract: In this study of the access process in analogical problem solving, preschoolers, first graders and third graders repeatedly listened to a variety of similar types of source stories until they could recall them completely. They then listened to a target story, were asked to retrieve the source story, were directed to solve a problem in a target story and to verify their responses. We found the following developmental differences: (1) the child could not access structural similarity at all; or the child could no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The combined regression analyses indicated that the processes underlying transfer were different for the children who were read the real story and the children who were read the fantasy story. The factors that predicted transfer for the children read the real story were similar to those documented by previous research (e.g., Brown et al, 1986;Crisafi & Brown, 1986;Daehler & Chen, 1993;Goswami, 2001;Holyoak et al, 1984;Kim & Choi, 2003;Richert et al, 2009;Richland, Morrison, & Holyoak, 2006;Singer-Freeman, 2005;Tunteler & Resing, 2002): age and memory for the solution-relevant parts of the source story. In contrast, children who were read the fantasy story were most likely to transfer solutions if they were read the story oneon-one with the experimenter, if they had low fantasy orientation, and if they had higher cognitive ability scores.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The combined regression analyses indicated that the processes underlying transfer were different for the children who were read the real story and the children who were read the fantasy story. The factors that predicted transfer for the children read the real story were similar to those documented by previous research (e.g., Brown et al, 1986;Crisafi & Brown, 1986;Daehler & Chen, 1993;Goswami, 2001;Holyoak et al, 1984;Kim & Choi, 2003;Richert et al, 2009;Richland, Morrison, & Holyoak, 2006;Singer-Freeman, 2005;Tunteler & Resing, 2002): age and memory for the solution-relevant parts of the source story. In contrast, children who were read the fantasy story were most likely to transfer solutions if they were read the story oneon-one with the experimenter, if they had low fantasy orientation, and if they had higher cognitive ability scores.…”
Section: Discussionsupporting
confidence: 81%
“…Given that the participants were primarily Hispanic and from low‐income preschools, a sample different from samples in previous research on analogical transfer, it is important to note that the analogical transfer rate for children in Study 1 (55.9% transferred at least one analogical solution) was consistent with transfer rates reported in previous research. Past research has suggested that preschool children transfer anywhere from 18% of the time (Kim & Choi, 2003) to 58% of the time (Holyoak et al., 1984). The lower rates of transfer in the classroom condition of Study 2 (27.5% of children transferred at least one of the analogical solutions) are not inconsistent with the lower end of previously reported transfer rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are certain contextual factors that are related to high rates of transfer, such as short and simple narratives (Goswami, ; Holyoak et al, ; Singer‐Freeman, ; Tunteler & Resing, ), and familiarity of or relationships with characters in the initial context (Lauricella, Gola, & Calvert, ). Because analogical transfer involves (a) recall or memory of the initial problem, (b) recognition of the relations between the initial and new contexts, and (c) transfer of the information from the initial to the new contexts, there are individual child factors related to successful analogical transfer of information from media contexts to the world outside of the digital screen, including memory of the initial situations and recognizing analogical similarities between contexts (Brown, Kane, & Echols, ; Goswami, ; Holyoak et al, ; Kim & Choi, ; Schlesinger et al, ).…”
Section: Learning and Transfermentioning
confidence: 99%
“…In other words, it transfers knowledge from a familiar situation to a less-familiar situation that requires explanation (Casakin and Goldschmidt, 1999). Analogical reasoning could also process from unfamiliar to familiar, for example, exploring a new (unfamiliar) problem through identifying or recognizing similarities from a known (familiar) problem (Kim and Choi, 2003).…”
Section: Related Workmentioning
confidence: 99%